CDK14/β‐catenin/TCF4/miR‐26b positive feedback regulation modulating pancreatic cancer cell phenotypes in vitro and tumor growth in mice model in vivo. (20th December 2021) - Sun, Yunpeng; Wang, Pengfei; Zhang, Qiyu; Wu, Huanhuan
Abstract: Introduction: Chemotherapy and radiotherapy have been reported to be basically ineffective for pancreatic ductal adenocarcinoma patients; thus, gene therapy might provide a novel approach. CDK14, a new oncogenic member of the CDK family involved in the pancreatic cancer cell response to gemcitabine treatment, has been reported to be regulated by microRNAs. In the present study, we aimed to investigate whether miR‐26b regulated CDK14 expression to affect the phenotype of pancreatic cancer cells. Methods: Overexpression or knockdown of CDK14 or miR‐26b was generated in pancreatic cancer cell lines and the function of CDK14 and miR‐26b on cell phenotype and the Wnt signaling pathway was determined using 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide, 5‐ethynyl‐2′‐deoxyuridine and transwell assays, as well as a xenograft model and western blotting. The predicted binding site between the 3′‐untranslated region of CDK14 and miR‐26b, miR‐26b promoter and TCF4 was verified by luciferase or chromatin immunoprecipitation assays. Results: CDK14 overexpression inhibited p‐GSK3β, whereas it promoted p‐LRP6, the nuclear translocation of β‐catenin and the transactivation of TCF4 transcription factor, thus promoting pancreatic cancer cell aggressiveness. miR‐26b directly targeted CDK14 and inhibited CDK14 expression. In vitro and in vivo, miR‐26b overexpression inhibited, and CDK14 overexpression promoted, cancer cell aggressiveness; CDK14 overexpression partially attenuated the miR‐26b overexpression effects on cancer cells. The effects of miR‐26b overexpression on tumor growth and the Wnt/β‐catenin/TCF4 signaling were partially reversed by CDK14 overexpression. TCF4 inhibited the expression of miR‐26b by targeting its promoter region. Conclusions: CDK14, β‐catenin, TCF4 and miR‐26b form a positive feedback regulation for modulating pancreatic cancer cell phenotypes in vitro and tumor growth in vivo . Abstract : CDK14 might promote Wnt/β‐catenin/TCF4 signaling pathway to promote pancreatic cancer development. miR‐26b was regarded as a new therapeutic candidate of pancreatic cancer that might targeted inhibited CDK14 expression. TCF4 could affect the transcription of miR‐26b and form a regulatory loop with CDK14 to regulate the growth and migratory capacity of pancreatic cancer.